Performance of International Retailers: Empirical Evidence of an S-Curve Relationship. Issue 3 (27th May 2019) - Dimitrova, Boryana V.; Kim, Saejoon; Smith, Brent
Abstract: The performance outcomes of retail internationalization have attracted considerable scholarly interest, but studies have offered differing perspectives and findings on this relationship. In an effort to fill this gap on the topic, we posit that the relationship between the degree of retail internationalization and performance exhibits an S-curve shape. Using a sample of 18 international retailers with operations on six continents for the period 2001–2015, we find evidence of the S-curve dynamic where international retailers tend to experience declining performance after initial expansion beyond the home market, improving performance with continued expansion, and declining performance with further international expansion. We also examine two moderating variables on this relationship—foreign market growth and store format diversification. Our findings show that foreign market growth reinforces the hypothesized S-curve relationship while store format diversification reverses it. We offer theoretical and managerial implications based on the results of our study.